2011
DOI: 10.4067/s0717-95022011000200004
|View full text |Cite
|
Sign up to set email alerts
|

Phenytoin-induced Toxicity in the Postnatal Developing Cerebellum of Wistar Rats, Effect of Calotropis procera on Histomorphometric Parameters

Abstract: . Phenytoin-induced toxicity in the postnatal developing cerebellum of Wistar rats, effect of Calotropis procera on histomorphometric parameters. Int. J. Morphol., 29(2):331-338, 2011. SUMMARY:The role of methanolic leaf extracts of Calotropis procera in phenytoin-induced toxicity on histomorphometric variables in the postnatal developing cerebellum of Wistar rat was studied. Pregnant rats were treated orally with 50 mg/kg phenytoin in pre and post natal life and 300 mg/kg methanolic leaf extract of Calotropis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…Calotropis procera leaf extract has been reported to posses antioxidant activity by increasing the glutathione levels and decreasing the rate at which lipid peroxidation occurred in the developing cerebellum (Imosemi et al, 2010), preventing delayed maturation of cells of the cerebellar cortex and depletion of Purkinje cells of the developing cerebellum in phenytoin-induced oxidative stress (Imosemi & Osinubi, 2011). And that the antioxidant property of Calotropis procera was comparable to standard antioxidants, vitamins C and E.…”
Section: Introductionmentioning
confidence: 78%
“…Calotropis procera leaf extract has been reported to posses antioxidant activity by increasing the glutathione levels and decreasing the rate at which lipid peroxidation occurred in the developing cerebellum (Imosemi et al, 2010), preventing delayed maturation of cells of the cerebellar cortex and depletion of Purkinje cells of the developing cerebellum in phenytoin-induced oxidative stress (Imosemi & Osinubi, 2011). And that the antioxidant property of Calotropis procera was comparable to standard antioxidants, vitamins C and E.…”
Section: Introductionmentioning
confidence: 78%
“…They help in guiding migrating immature neurones; extending through the intermediate zone to the pial region, they form the scaffold for Purkinje and other cells moving from the ventricular zone to their proper positions during embryogenesis [ 37 ]. Disorganization of the Bergmann glial cells, therefore, disrupted the migration of the young neurones [ 38 ], as has been observed in the delayed migration of the external granular cells [ 39 41 ]. It has been suggested that Bergmann glial fibres may be responsible for directing the geometrical organization of the cerebellar constituents [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The thickness of EGL increases for approximately 10 days, then reduces, with the molecular layer replacing it. At postnatal day 21, it is expected for the EGL to have virtually disappeared, with molecular layer extending from the Purkinje cell layer to the pial surface [ 39 , 58 , 59 ]. This reduced radial migration of external granular cells through the molecular layer is a component of impaired cerebellar development [ 60 , 61 ] resulting in hypercellular molecular layer [ 59 ], and this could cause abnormalities of movement and balancing in kola nut-treated rats.…”
Section: Discussionmentioning
confidence: 99%
“…Ding et al (2013) reported a decreased thickness of the cerebellar EGL on postnatal days 10 and 13 rats treated with arsenic. The thicker EGL observed in the arsenic-treated pups on day 14 may be due to delayed differentiation of the EGL because the EGL is a highly metabolic layer which disappears in humans at approximately two years of age and in mouse, at about days 20 (Hatten and Heintz, 1995;Altman and Bayer, 1985;Imosemi and Osinubi, 2011;Butts et al, 2014). The external granular layer (EGL) consists of highly metabolic cells whose differentiations result in the synthesis of the outer stellate, basket, Golgi type II and granule cells of the cerebellar cortex.…”
Section: Discussionmentioning
confidence: 99%
“…The nervous system, in which the cerebellum is an important part of, is one of the earliest systems to develop embryologically but completes its developmental process postnatally (Hill et al, 2018), and as a result, it is highly prone to any form of injury in prenatal and postnatal life. The cerebellum lies in the posterior cranial fossa of the cranial cavity and functions in the control of smooth and skilful movements, balance, and higher cognitive and emotional functions (Hall et al, 1995;Imosemi and Osinubi, 2011;Hashimoto and Hibi, 2012;Buckner, 2013;Balaei et al, 2017). The cerebellum is highly susceptible to oxidative stress during prenatal and perinatal periods (Lopez, et al, 2009).…”
Section: Introductionmentioning
confidence: 99%